2020
DOI: 10.1177/1035719x20971853
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation in the Australian Public Service: Formerly practised – Not yet embedded

Abstract: This article examines what impeded programme evaluation from being embedded in the Australian Public Service (APS), being relevant to the Australian Government’s current priority of embedding evaluation in the APS. It draws on a case study of evaluation as the major element of the 1980s APS ‘Managing for Results’ (MfR) reform and the reasons for evaluation’s later demise. During MfR, evaluation was intended to demonstrate the effectiveness of APS programmes. Although evaluation was incorporated into APS practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…• The lack of incentive to evaluate programs in an environment where governments and ministers were seen to want to increase their control of the public service and minimise scope for criticism (Graves 2020;Halligan 2020). • The discretion secretaries have in choosing whether to evaluate programs or not (Gruen 2018;Graves 2020), and departments' preference for using other performance measures such as case studies and quantitative information, which are less troublesome. • The high turnover of secretaries in the APS, which undermines the embedding of public administration reforms, added to the lack of evaluation skills (Graves et al 2021).…”
Section: Morrisonmentioning
confidence: 99%
See 1 more Smart Citation
“…• The lack of incentive to evaluate programs in an environment where governments and ministers were seen to want to increase their control of the public service and minimise scope for criticism (Graves 2020;Halligan 2020). • The discretion secretaries have in choosing whether to evaluate programs or not (Gruen 2018;Graves 2020), and departments' preference for using other performance measures such as case studies and quantitative information, which are less troublesome. • The high turnover of secretaries in the APS, which undermines the embedding of public administration reforms, added to the lack of evaluation skills (Graves et al 2021).…”
Section: Morrisonmentioning
confidence: 99%
“…Despite a plethora of evaluation policies, reviews, commentaries and implementation practices, as shown in Table 12.1, while there have been bright spots of government support since 1990, evaluation has struggled to become a sustained and effective part of public administration in the Australian Government over the last 40 years (Graves 2020).…”
mentioning
confidence: 99%
“…Evaluation of APS programs was part of the 1980s reforms through Managing for Results initiatives, linking policy with implementation for outcomes. Although embedded in APS practice in 1992, the requirement for formal evaluation was discontinued in 1997, before once again becoming flagged as a future priority following the 2018-19 APS Review (Graves, 2020).…”
Section: Early Years From the 1970smentioning
confidence: 99%